Theopoetics from Below: A South African Black Christological Encounter with Radical Theology - Ullrich, Calvin D. 1990- (2021)
Given the evidence of Black suffering more than two and half decades after apartheid, this paper proceeds on the premise that theology cannot continue as business per usual. It attempts to stage a critical and creative encounter between the radical theology of the philosopher, John D. Caputo and the liberation Christology of the South African theologian, Takatso Mofokeng. It demonstrates both the commonalities and limits of their respective accounts and suggests that radical theology and liberation Christology supplement each other in critically-constructive ways. Liberation Christology’s criticism of power, institution, and Western modes of theological discourse, which it shares with radical theology, supplements the latter’s somewhat abstract account of “the event” with the particularity of Black experience. Radical theology, on the other hand, offers Black Christology a way to be critical of its own metaphysical claims, as well as its tendency to mimic the oppressor in its categories of positive identification.
Keywords: John D. Caputo; Takatso Mofokeng; Christology; Liberation Theology; Radical Theology